Design and Numerical Analysis of a Horizontal Axis Wind Turbine - Pradhan, Shrayas; Chitrakar, Sailesh (Kathmandu University Journal of Science, Engineering and Technology, 2022)
In this paper, mathematical design of a 20 kW horizontal axis wind turbine is conducted along with computational analysis to verify the performance of the designed blade. Blade Element Momentum (BEM) theory is used for the design of blades, empirical BEM relations for geometry calculations for twist distribution and chord distribution are included. The computational analysis on the performance of the geometric design is done using both BEM and Computational Fluid Dynamics (CFD) through Qblade BEM code and ANSYS CFX tool respectively. The rotational periodicity based domain is used for CFD computation and k- ϵ turbulence model is considered. The analysis is done in variable speed conditions (constant tip speed ratio of 6) for wind speed range 2-12 m/s, and change of pitch angles from 1 to 4°. The optimum pitch is obtained as 3° from CFD analysis. The results of torque, Cp/Power, velocity streamlines, and pressure contours are obtained from CFD. Torque curve obtained from BEM and CFD analysis over wind speeds 2-12 m/s showed good agreement, supporting the HAWT geometric design. A maximum Cp of 0.399 was obtained at 12 m/s.